UJI BEBERAPA MINYAK ATSIRI SEBAGAI ATRAKTAN LALAT BUAH (Bactrocera sp.) PADA TANAMAN TOMAT) - ARIYANTI, EKA LESTARI; SAYANG, YULIS; A, SYAMSURIATI (Jurnal Agroteknos, 2022)
This research was conducted to determine the effectiveness of this type of essential oil as an attractant for fruit flies (Bactrocera sp.) on tomato plants. The research was carried out on farmer's land in Benteng Alla Utara Village, Baroko District, Enrekang Regency. The implementation of this research starts from April 2021 until it is finished. This experiment used a randomized block design (RBD) consisting of five treatments with four replications. The treatments included citronella essential oil, clove essential oil, basil essential oil, tomato extract and also control. In testing the effectiveness of several essential oils obtained by steam distillation distillation technique. Each trap dripped with 3 ml of essential oil. Observation of trapped fruit fly populations was carried out on plants 49 days, 56 days, 63 days, 70 days, 77 days, and 84 days after planting. The results showed that the essential oil of basil was the most effective as an attractant for fruit flies on tomato plants with an average population of 55.17%.